APPLICATION OF DISCOVERY LEARNING MODELS TO LIGHT MATERIALS TO IMPROVE STUDENT LEARNING OUTCOMES - Kristina Uskenat; Kadek A.C Adelia (Jambura Physics Journal, 2021)
This study aims to describe the results of the application of the discovery learning model on the subject matter of light in class VIIIC students of SMP Negeri 8 Kupang even semester of the 2019/2020 academic year. This research is descriptive. This research was conducted at SMP Negeri 8 Kupang for the 2019/2020 school year. The subjects in this study were researchers and 22 students of class VIIIC at SMP Negeri 8 Kupang, even semester, 2019/2020 academic year. The techniques used to collect data in this study are observation and tests. Based on the results of the descriptive analysis of the research data, it shows that in general, the application of the discovery learning model for the subject matter of light for students is optimal. In detail, the researcher's ability to manage to learn is obtained which includes: planning, implementing, and evaluating learning, including in the good category. The learning outcomes test (THB) of students for cognitive learning outcomes tests on learning implementation activities which include: preliminary activities, core activities, closing activities, time allocation, and class atmosphere are all in the very high category and cognitive achievement for each lesson plan is all complete.